1995
DOI: 10.1063/1.114051
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and electroluminescence of SiGe dots fabricated by island growth

Abstract: We present a study of photo- and electroluminescence of SiGe dots buried in Si and compare them with structures containing smooth SiGe layers. The SiGe dot structures were fabricated by low-pressure chemical vapor deposition using the Stranski–Krastanov growth mode (island growth). We show that the localization of excitons in the dots leads to an increase of the luminescence efficiency at low excitation compared to smooth SiGe layers (e.g., quantum wells). At higher excitation the efficiency decreases which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 254 publications
(97 citation statements)
references
References 0 publications
2
93
0
2
Order By: Relevance
“…2 The emission was near ϭ1.3 m and persisted up to 200 K. Since then, emission was improved by more than 100 times using structures with nominal pure Ge. 3,4 This was due to the increased valence band offset of the Ge/Si heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…2 The emission was near ϭ1.3 m and persisted up to 200 K. Since then, emission was improved by more than 100 times using structures with nominal pure Ge. 3,4 This was due to the increased valence band offset of the Ge/Si heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…The lower energy conduction band is solely considered, that corresponds to the six-fold ∆ , four-fold 4 ∆ and two-fold 2 ∆ degenerated valleys for Si 1−y Gе y injecting contacts, Si 1−x Gе x potential barriers and Si quantum wells region, respectively (see Ref. [11]).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Although III-V compounds, such as InGaAs latticematched to InP, offer superior optical performance over the Si-based ones in photodetectors at wavelengths near 1.3 and 1.55 µm for optical fiber communications [1], the compatibility of silicon materials with the state-of-the-art VLSI technology stimulates a great number of research efforts to take advantage of the feasibility of photodetectors with wavelengths beyond the limitation of the Si band gap, to 1.3 µm and even to 1.5 µm [2,3]. Recent advances in Si low-temperature epitaxy such as molecular beam epitaxy (MBE) and ultra-high vacuum chemical vapor deposition (UHV-CVD) enable the incorporation of Ge into Si to form high quality SiGe alloys, and thus to extend the spectral response to this wavelength range [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that dislocation-free SiGe growth can be achieved using a higher temperature (≥600 o C), and that the non-planar geometry is mainly responsible for the significant increase of the SiGe critical layer thickness [5]. It has also been found that, compared to two-dimemensional (2D) Si/SiGe NSs, the PL and electroluminescence (EL) quantum efficiency in 3D Si/SiGe NSs is higher (up to ~1%), especially for T > 50 K [6][7][8][9]. Despite many successful demonstrations of PL and EL in the spectral range of 1.3-1.6 m, which is important for optical fiber communications, the proposed further development of 3D Si/SiGe based light emitters was discouraged by several studies indicating a type II energy band alignment at Si/SiGe heterointerfaces [10], where the spatial separation of electrons (located in Si) and holes (localized in SiGe) was thought to make carrier radiative recombination very inefficient.…”
mentioning
confidence: 90%